Reply to Comment by F. Kenig, L. Chou, and D. J. Wardrop on "Evaluation of the Tenax Trap in the Sample Analysis at Mars Instrument Suite on the Curiosity Rover as a Potential Hydrocarbon Source for Chlorinated Organics Detected in Gale Crater" by Miller et al., 2015. Issue 2 (14th February 2019) - Summons, Roger E.; Miller, Kristen E.; Kotrc, Benjamin; Belmahadi, Imene; Buch, Arnaud; Eigenbrode, Jennifer L.; Freissinet, Caroline; Glavin, Daniel P.; Szopa, Cyril
Abstract: Kenig et al. comment on our 2015 reporting of laboratory analog experiments aimed at testing the stability of the hydrocarbon trap material used in the Sample Analysis on Mars (SAM) instrument on board the Curiosity Rover operating in Gale Crater on Mars. They propose chemical structures for some decomposition products of the Tenax TA polymer when it is exposed at high temperatures to the Cl2 and O2 gases formed by the thermal decomposition of perchlorate. Further, Kenig et al. propose that these decomposition products accumulate and then react further in cooler downstream sections of the SAM analytical pipeline to produce the chlorobenzene that was detected in the Cumberland mudstone of Gale Crater. However, numerous experiments conducted in the laboratory show that Tenax TA decomposition products only appear after repeated exposure to much higher levels of Cl2 and O2 than those seen by the flight instrument. Moreover, the sequence of chlorobenzene detections during gas chromatography‐mass spectrometry experiments conducted on Mars cannot be explained by Tenax TA decomposition, nor can the detection of chlorobenzene in Evolved Gas Analysis experiments that involve pathways devoid of Tenax TA. Kenig et al. are incorrect in their assertion that Tenax TA decomposition products can account for the chlorobenzene detected on Mars by SAM. Plain Language Summary: Calcium and magnesium salts of chlorate and perchlorate have been detected in surface sediments on Mars. The presence of these compounds, which emit corrosive gases when heated to high temperatures, can potentially compromise experiments aimed at detecting organic carbon compounds in Mars sediments. Perchlorate decomposition products also have the potential to damage components, namely the hydrocarbon trap, used in the construction of the Sample Analysis on Mars on instrument the Curiosity rover. In earlier work, we evaluated this possibility and provided evidence that the hydrocarbon trap was stable unless exposed to high concentrations of corrosive gases far beyond those that would be seen by the instrument operating on Mars. Experiments conducted by the SAM instrument have detected several organic compounds, including chlorobenzene, which cannot be explained by decomposition of organic materials carried on flight instrument. In particular, chlorobenzene was detected in the Cumberland mudstone in experiments that used pathways that did not include exposure to a hydrocarbon trap. Key Points: Kenig et al. (2019) speculate on the chemical structures and subsequent fate of two unknown compounds produced during repetitive laboratory testing of the Tenax TA polymer used in the SAM instrument on board the Curiosity Rover They further speculate that Tenax TA decomposition products are the source of chlorobenzene detected by SAM in experiments on Mars Multiple lines of evidence show that chlorobenzene identified by SAM in Cumberland samples comes from an indigenous carbon source including Evolved Gas Analysis experiments that do not involve any sample contact with Tenax TA